Length and weight of F0 wild-caught adults Gasterosteus aculeatus (males and females) used for breeding in heatwave experiment - Spence-Jones, Helen; Shama, Lisa N S (In: Spence-Jones, H; Shama, LNS (2025): Stickleback (Gasterosteus aculeatus) marine heatwave experiment: F0 adult size and fecundity traits, F1 offspring growth, behavior and survival, and F2 offspring egg size, clutch size, and hatchling length [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.973487, 2025)
Fish were brought to the laboratory at the AWI Wadden Sea Station Sylt and used as breeding adults for a multi-generation laboratory experiment investigating the effects of marine heatwaves on stickleback fitness-related traits. These F0 generation wild-caught adults (males and females) were acclimated to three heatwave scenarios (no heatwave control, single heatwave or double heatwave) for three months before breeding (starting 12 June 2022) via artificial fertilization.
Keywords: clutch size; egg diameter; Experiment; fertilization success; Gasterosteus aculeatus; hatching success; Laboratory experiment; Length; stickleback; Weight